The Effect of Staphylocoagulase on the Subunit Structure of Human Fibrin - Tager, M; King, M. J. S (Thrombosis and Haemostasis, 1974)
Fibrin clots resulting from the action of coagulase thrombin were subjected to Polyacrylamide gel electrophoresis in the presence of hirudin or of heparin to exclude the action of biothrombin.Alpha, beta, and gamma polypeptide chains were resolved not differing from those induced by the action of thrombin on fibrinogen.No evidence was found of any further degradation of any of the polypeptide chains.Although coagulase thrombin fails to activate factor XIII at calcium ion concentrations effective for the cross-linking of fibrin by thrombin, higher concentrations of calcium lead to the activation of factor XIII by coagulase thrombin, resulting in gamma dimer formation.The data support the evidence that coagulase thrombin, like biothrombin, acts as a limited proteolytic agent on fibrinogen.